Şırnak ilinde yaşayan 3 kuşağın dini tutumu ve gidişatı üzerine nitel bir araştırma - Arıç, Zeynep (My University, 2023)
Belirli bir zaman diliminde doğan ve benzer olayları tecrübe eden, bireylerden meydana gelen grupları tanımlamak için kuşak kavramı kullanılmaktadır. Aynı kuşağa mensup bireylerin dini tutum ve davranışlarında benzerlikler ve farklılıklar görülmektedir. Bireylerin mensubu olduğu kuşak kadar yaş faktörü de dini tutum ve davranışları üzerinde etkilidir. Bu tezde Şırnak ilinde yaşayan aynı aileye mensup üç kuşağın dini tutum ve davranışları tespit edilmeye çalışılmıştır. Bu amaçla üç kuşağa mensup dede/ nene, anne/ baba ve evlatlarla yüz yüze derinlemesine görüşmeler yapılmış din, dindarlık, inanç, dua, ibadet, dinin günlük hayata etkileri, dini tecrübe, zorluk anında bireylerin başa çıkma yöntemleri ve diğer kuşakların dindarlıklarına yönelik tutumlarının tespit edilmesi hedeflenmiştir. Araştırma verilerin toplanmasında dokümantasyon ile yarı yapılandırılmış görüşme tekniği kullanılmıştır. Her kuşaktan 15 kişi olmak üzere üç kuşaktan toplamda 45 kişiyle yapılan görüşmelerden elde edilen bulguları sonucunda üç kuşağın dini tutum ve davranışlarında farklılık ve benzerlikler tespit edilmiştir. Ayrıca kuşak kavramının yanında bireyin mensubu olduğu yaş aralığının da bireylerin dini tutum ve davranışları üzerinde belirleyici bir role sahip olduğu görülmüştür

The concept of generation is used to describe groups of individuals who were born in a certain period and who experience similar events. There are similarities and differences in the religious attitudes and behaviors of individuals belonging to the same generation. As well as the generation to which individuals belong, the age factor is effective on their religious attitudes and behaviors. In this thesis, the religious attitudes and behaviors of three generations belonging to the same family living in Şırnak province tried to be determined. For this purpose, face-to-face in-depth interviews were conducted with grandparents, mothers/ fathers, and children belonging to three generations to determine their attitudes towards religion, religiosity, belief, prayer, worship, the effects of religion on daily life, religious experience, coping methods of individuals in times of difficulty and the religiosity of other generations. To collect the data, documentation and semi-structured interview techniques were used. As a result of the findings obtained from the interviews with a total of 45 people from three generations, 15 from each generation, differences and similarities were found in the religious attitudes and behaviors of the three generations. In addition to the concept of generation, it was also seen that the age range to which the individual belongs has a determining role in the religious attitudes and behaviors of individuals
Keywords: dimensions of religiosity; Din; dindarlığın boyutları; dindarlık; Dini yaşam; generation concept; generation theory; kuşak kavramı; kuşak teorisi; Religion; religiosity; Religious life; Şırnak (Turkey); Şırnak (Türkiye)